Everyday Objects, Affect, and Embodied Policy: A Case Study of Popular Music Summer Camps during COVID-19 - Rush, Kayla (Irish Journal of Arts Management and Cultural Policy, 2023)
In 2021, summer camps represented, for many children and teenagers, a much desired return to ‘normal’ social interactions, following school disruptions due to the COVID-19 pandemic. One such summer camp programme was coordinated by Rock Jam, a private popular music education organisation based in Dublin. Rock Jam’s summer camps were booked to capacity, with both children and their parents or guardians eager for a return to face-to-face educational and social experiences. However, early in July, summer camp programming became more complicated when the Irish Government clarified that indoor summer camps were not permitted, and all summer camp activities must be held outdoors due to public health restrictions. This article reports on Rock Jam’s pandemic response measures, both before and after the policy clarification. It reflects on and examines the ways in which policies are embodied and materialised in everyday interactions, focusing especially on the outdoor tents that allowed the summer camps to continue in compliance with the newly clarified policy. It uses the language of affect to examine the sensory, emotional, material, and interpersonal dimensions of these everyday interactions with embodied policy.